Comparison of the platelet activation status of single‐donor platelets obtained with two different cell separator technologies. Issue 9 (29th July 2020) - Millar, Daniel; Hayes, Chelsea; Jones, Jessica; Klapper, Ellen; Kniep, Joel N.; Luu, Hung S.; Noland, Daniel K.; Petitti, Laura; Poisson, Jessica L.; Spaepen, Erik; Ye, Zhan; Maurer‐Spurej, Elisabeth
Abstract: Background: The microparticle content (MP%) of apheresis platelets—a marker of platelet activation—is influenced by donor factors and by external stressors during collection and storage. This study assessed the impact of apheresis technology and other factors on the activation status (MP%) of single‐donor apheresis platelets. Study Design and Methods: Data from six US hospitals that screened platelets by measuring MP% through dynamic light scattering ( ThromboLUX ) were retrospectively analyzed. Relative risks (RRs) were derived from univariate and multivariable regression models, with activation rate (MP% ≥15% for plasma‐stored platelets; ≥10% for platelet additive solution [PAS]‐stored platelets) and MP% as outcomes. Apheresis platform ( Trima Accel vs Amicus ), storage medium (plasma vs PAS), pathogen reduction, storage time, and testing location were used as predictors. Results: Data were obtained from 7511 platelet units collected using Trima (from 16 suppliers, all stored in plasma, 20.0% were pathogen‐reduced) and 2456 collected using Amicus (from four different collection facilities of one supplier, 65.0% plasma‐stored, 35.0% PAS‐stored, none pathogen‐reduced). Overall, 30.0% of Trima platelets were activated compared to 45.6% of Amicus platelets ( P < .0001). Multivariable analysis identified apheresis platform as significantly associated with platelet activation, with a lower activation rate for Trima than Amicus (RR: 0.641, 95% confidence interval [CI]: 0.578; 0.711, P < .0001) and a 6.901% (95% CI: 5.926; 7.876, P < .0001) absolute reduction in MP%, when adjusting for the other variables. Conclusion: Trima ‐collected platelets were significantly less likely to be activated than Amicus ‐collected platelets, irrespective of the storage medium, the use of pathogen reduction, storage time, and testing site.